Individual differences in perceiving and recognizing faces- one element social cognition .[article]. - Wilhelm, Oliver
Recognizing faces swiftly and accurately is of paramount importance to human as a social species. Individual differences in the ability to perform these tasks may therefore reflect important aspects of social or emotional intelligence. Although functional models of face cognition based on group and single case studies postulate multiple component processes, little is known about the ability structure underlying individual differences in face cognition. In 2 large individual differences experiments (N=151 and N=209), a broad variety of face-cognition task were tested and the component abilities of face cognition-face perception, face memory, and the speed of face cognition-were identified and then replicated. Experiment also showed that the 3 face-cognition abilities are clearly distinct from immediate and delayed memory, mental speed, general cognitive ability, and object cognition. These results converge with functional and neuroanatomical models of face cognition by demonstrating the difference between face perception and face memory. The results also underline the importance of distinguishing between speed and accuracy of face cognition. Together our results provide a first step toward establishing face-processing abilities as an independent ability reflecting elements of social intelligence. -- (from the author)